2020
DOI: 10.3389/fimmu.2020.01272
|View full text |Cite
|
Sign up to set email alerts
|

In vitro IL-6/IL-6R Trans-Signaling in Fibroblasts Releases Cytokines That May Be Linked to the Pathogenesis of IgG4-Related Disease

Abstract: Background: The remarkable mechanisms of storiform fibrosis and the formation of high levels of IgG4 with a pathogenic germinal center (GC) in the inflammatory tissue of IgG4-RD remains unknown and may be responsible for the unsatisfactory therapeutic effect on IgG4-related diseases when using conventional therapy. Objectives: To investigate the mechanisms of interleukin 6 (IL-6) inducing fibroblasts to produce cytokines for pathogenic GC formation in the development of IgG4-related disease (IgG4-RD). Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 70 publications
(106 reference statements)
1
20
0
Order By: Relevance
“…Clinicopathologically, increased IL-6 levels were reported in IgG4-RD [ 16 ] and IL-6 was elevated in IgG4-related dacryoadenitis and sialadenitis [ 17 ]. The reason for high IL-6 levels in IgG4-RD is not well understood, but IL-6 is thought to directly promote the development of fibrosis in damaged tissues [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinicopathologically, increased IL-6 levels were reported in IgG4-RD [ 16 ] and IL-6 was elevated in IgG4-related dacryoadenitis and sialadenitis [ 17 ]. The reason for high IL-6 levels in IgG4-RD is not well understood, but IL-6 is thought to directly promote the development of fibrosis in damaged tissues [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we showed that IL-6 could promote the pathogenesis of IgG4-RD by inducing fibroblasts releasing Tfh and B cell differentiation factors. 8 However, the therapeutic effect of the IL-6R antibody tocilizumab on IgG4-RD has not been reported to date, and the effectiveness of tocilizumab has only been reported in several retroperitoneal fibrosis and chronic periaortitis cases. 21 , 22 Retroperitoneal fibrosis and chronic periaortitis are thought to have overlap with IgG4-RD.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Therefore, in recent randomized controlled trials (RCTs) conducted in patients with IgG4-RD, attention has been paid to the effectiveness of steroid-sparing agents known as immunosuppressors. 7 9 It has been suggested that leflunomide or mycophenolate mofetil (MMF), used in combination with GCs, was superior to GC therapy alone. 7 , 8 A prospective study also indicated that the use of GCs plus cyclophosphamide (CYC) reduced the relapse rate better than did GCs plus MMF.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations